Istisykālāt Al Imām Al Syaṭibī Fi Juz`i Al Aḥkām Min Muwāfaqātihi (Dirāsaħ Tahlīlīyyaħ Naqdiyyaħ): استشكالات الإمام الشاطبي في جزء الأحكام من موافقاته (دراسة تحليلية نقدية) - Qasur, Mubarak Said Mubarak (PT. Student Rihlah Indonesia, 2024)
This research presented the complex issues mentioned by Imam Al-Shatibi in his book (Al-Muwafaqat, in the part of rulings). The author have clarified the nature of the complex issues to make it easy to benefit from the book. In addition, he come up with several important results such as the enrichment and neutrality of Al- Shatibi when dealing with complex issues. The results also concluded that Imam Al Shatibi's had extensive knowledge, compelling perceptions and sophisticated style The author have followed the same approach and manner of Al-shatibi and recommended to enrich the book with more research.